ANALISIS PERBANDINGAN METODE FUZZY INFERENSI SISTEM TSUKAMOTO DAN MAMDANI DALAM PENENTUAN ESTIMASI JUMLAH PRODUKSI GULA - Hadiyanti, Widya Anggraeni; Honggowibowo, Anton Setiawan; Suhayati, Maya (Sekolah Tinggi Teknologi Adisutjipto Yogyakarta, 2013)
PT Madu Baru Yogyakarta s a company that produces sugar. Many factors must be considered in determining the mount o f production generated annually. For that, in determining the mount of production per year required and analysis of decision support systems analysis will be done applying Method of Fuzzy Inference System Tsukamoto end Method Inference System Mamdani using the min as function o f its implications, the from each rule give nextplicitly (scrip) by the smallest degree of membership (Defuzzifikasi), the final result by applying a weighted average for Fuzzy Inference System defuzzyfikasi begins the composition rules between Max and the Method apllied taking the center point (z*) fuzzy area. With the comparison method of Fuzzy Inference System and Method of Fuzzy Inference System Mamdani, obtained the most appropriate methods and approaches in determining the estimated amount o f sugar production, in order to obtain an output that is the amount o f sugar per year.With statistical tests, it can be concluded that the method is relatively close to the calculation method of the factory is Tsukamoto, because the method o f Tsukamoto had a lower mean than the mean on the 7,960.42 Mamdani methods is 21710.14.